Literature of ReviewThe Influence of Product Variations, Celebrity Endorsers and Brand Trust on Purchasing Decisions in Make Over Cosmetic Brands (Case Study of Bhayangkara Jaya University Students) - Amelia Putri (Draf Solusi Indonesia, 2023)
This research aims to examine the influence ofProduct Variations, Celebrity Endorsers and BrandTrust on Purchasing Decisions. This research focuseson Make Over Cosmetic users. This research will becarried out at Bhayangkara University, Jakarta Raya,where the target respondents are students who usethese products and brands. This research will usequantitative methods as a research approach with apreviously known population and sample. Thisresearch also adopted several previous studies inanalyzing data using SPSS 28